The Law of Bahaupan Contracts During The Covid-19 Pandemic (Study in Banjarmasin City) - Faridah Faridah; Rahmat Fadillah (Syariah: Jurnal Hukum dan Pemikiran, 2022)
During the co-19 pandemic there were many obstacles in the economy, inevitably also in the Banjarmasin City area of South Kalimantan Province, various efforts were made to maintain the course of the economy in this region, all strategies were carried out, but it seems that there is still one contract system that can still survive, namely the Bahaupan contract system which is a contract system owned by the Banjar community in Banjarmasin City. This research is empirical research with a legal sociology approach, through the medium of direct observation and interviews in the field to economic entrepreneurs during the Covid-19 pandemic. Some of the results found are: Akad Bahaupan can still be used during the Pandemic, entrepreneurs use the latest methods in managing their businesses during the Pandemic, and still always increase prudence in carrying out economic activities. Dimasa pandemi covid-19 banyak sekali terjadi kendala dalam perekonomian, tidak terelakkan juga pada wilayah Kota Banjarmasin Provinsi Kalimantan Selatan, berbagai upaya dilakukan untuk mempertahankan jalannya perekonomian di wilayah ini semua strategi dijalankan, akan tetapi nampaknya masih ada satu sistem akad yang masih dapat bertahan, yaitu sistem akad Bahaupan yang merupakan sistem akad yang dimiliki oleh masyarakat Banjar di Kota Banjarmasin. Penelitian ini bersifat penelitian empiris dengan pendekatan sosilogi hukum, melalui media observasi dan wawancara langsung di lapangan kepada para pengusaha ekonomi dimasa pandemi covid-19. Adapun beberapa hasil yang ditemukan adalah: Akad Bahaupan masih bisa digunakan dimasa Pandemi, para pengusaha menggunakan cara-cara terbaru dalam mengelola usahannya dimasa Pandemi, dan tetap selalu meningkatkan kehati-hatian dalam melangsungkan kegiatan perekonomian.